2013
DOI: 10.1016/j.egja.2012.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and effect of TIVA with propofol or dexmedetomidine versus sevoflurane without muscle relaxant during repair of the brachial plexus

Abstract: Background: Total intravenous anesthesia (TIVA) versus inhalational anesthesia was selected as the anesthetic method, in order to avoid the use of muscle relaxants during repair of brachial plexus injury. We designed this study to determine effect and efficacy of TIVA versus sevoflurane during repair of brachial plexus injury. Methods: Sixty patients scheduled for repair of injured brachial plexus from January 2009 till December 2011 were enrolled in this prospective, single-blind, randomized study. They recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Nevertheless, this meta-analysis has several limitations. First, only eight trials 3,[21][22][23]35,37,44,47 reported the source of their funding; and therefore, we did not know Fig. 6 Results of subgroup analysis of the incidence of postoperative shivering by routes of dexmedetomidine administration whether the other trials were supported by industry, which could make the design prone to show the drug in its best light.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, this meta-analysis has several limitations. First, only eight trials 3,[21][22][23]35,37,44,47 reported the source of their funding; and therefore, we did not know Fig. 6 Results of subgroup analysis of the incidence of postoperative shivering by routes of dexmedetomidine administration whether the other trials were supported by industry, which could make the design prone to show the drug in its best light.…”
Section: Discussionmentioning
confidence: 99%
“…3,9,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Other control agents included fentanyl, [33][34][35][36] remifentanyl, 37,38 meperidine, 15 midazolam, [39][40][41] propofol, 43,44 ketamine, 45,46 tramadol, 24,47 clonidine, 42 propacetamol, 48 and buprenorphine 49 ( 8 were reported in the 39 included trials, and all studies reported every endpoint mentioned in the Methods section (reporting bias). 8 however, some bias 8 may exist in of the two trials, 27,32 as the length of surgery was not clear.…”
Section: Study Characteristicmentioning
confidence: 99%
“…Dexmedetomidine is a highly effective and selective α 2-adrenergic receptor agonist, which manifests the effects of sedation, analgesia, anti-anxiety and sympathetic inhibition in a dose-dependent manner, with few side effects. At present, clinical research shows that dexmedetomidine can reduce the dose requirements for intravenous or inhalation anesthetics and opioids, and the hemodynamics is more stable during the operation 3 5 . However, there is no report on the effect of etomidate combined with dexmedetomidine on adrenocortical function in elderly patients.…”
Section: Introductionmentioning
confidence: 99%
“…Dexmedetomidine is a highly effective and selective α 2-adrenergic receptor agonist, which manifests the effects of sedation, analgesia, anti anxiety and sympathetic inhibition in a dose-dependent manner, with few side effects. At present, clinical research shows that dexmedetomidine can reduce the dose requirements for intravenous or inhalation anesthetics and opioids, and the hemodynamics is more stable during the operation [3,4,5]. However, there is no report on the effect of etomidate combined with dexmedetomidine on adrenocortical function in elderly patients.…”
Section: Introductionmentioning
confidence: 99%